Village Community Readiness In Estabilishing A Global Village - Eny Boedi Orbawati; Sujatmiko Sujatmiko; Fadlurrahman Fadlurrahman; Nike Mutiara Fauziah (Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
Global village is a phenomenon that occurs due to advances in information technology where there are no physical boundaries between individuals, communities, and countries. The world is connected through information technology and shares a variety of things. Apart from being a potential threat, the global village phenomenon also provides opportunities for introducing the Indonesian tourism sector to the global community. One of the villages that have the potential to exploit the global village phenomenon, especially in the tourism sector, is Ngargogondo Village, Borobudur Subdistrict, Magelang Regency, Central Java because it has the potential as a language tourism village. This study aims to measure community readiness in realizing a global village in the tourism sector with an analysis of community readiness dimensions in tourism and the global village aspect. This study used a survey approach with 157 respondents who were obtained using cluster random sampling technique. Meanwhile, the indicators used are adopted from the Tri-Ethnic for Prevention Research, with 19 indicators as research instruments. The results showed that the Ngargogondo Village community’s readiness was at the preparation stage (tourism aspect) and pre-planning (global village aspect). This study suggests that to increase community readiness in realizing the global village tourism sector, the Ngargogondo Village government must increase the availability of resources, especially in the tourism aspect, and create a positive climate in the community in response to the development of information technology in Ngargogondo Village.